Secondary School Leaving Examinations: The Impact of Expectancies, Values, and Dimensional Comparisons on Male and Female Students’ Science-Oriented Choices - Kampa, Nele; Krämer, Sonja; Hannover, Bettina (Frontiers in Education, 2020)
In Germany, secondary school students have to choose at least one STEM subject (mathematics, biology, chemistry, physics) for their Secondary School Leaving Examinations. In a representative sample of students in grade 13 in one federal state in Germany, we explore boys’ and girls' subject choices in an expectancy-value framework by considering students’ prior performance, ability self-concept, and values in the chosen subject. We extend previous research by including dimensional comparisons that students make between the varying subjects they have to choose from. We discriminate between two opposing groups. One group shows a science-avoidance choice pattern by selecting only one science subject: biology (n = 439). The other group shows a science-oriented choice pattern by selecting physics or chemistry or two STEM subjects of which one was at least physics or chemistry (n = 248). We measured achievement test scores, relative and absolute midterm grades, ability self-concepts as well as attainment and utility values in chosen and non-chosen subjects and calculated logistic regressions as well as multigroup models. Our results showed that science-oriented final exam choices depended highly on ability self-concept in mathematics for boys and girls and on the relative mathematics-English midterm grade for boys. When controlling for the other predictors, attainment and utility values seemed to be irrelevant for science-oriented final exam subject choice. Our findings raise the question whether boys and girls should be encouraged differently in order to stay in the STEM pipeline and how structural conditions may shape pathways into or out of this pipeline.